2016
DOI: 10.12659/msm.900992
|View full text |Cite
|
Sign up to set email alerts
|

Specific Features of Executive Dysfunction in Alzheimer-Type Mild Dementia Based on Computerized Cambridge Neuropsychological Test Automated Battery (CANTAB) Test Results

Abstract: BackgroundThe primary manifestation of Alzheimer’s disease (AD) is decline in memory. Dysexecutive symptoms have tremendous impact on functional activities and quality of life. Data regarding frontal-executive dysfunction in mild AD are controversial. The aim of this study was to assess the presence and specific features of executive dysfunction in mild AD based on Cambridge Neuropsychological Test Automated Battery (CANTAB) results.Material/MethodsFifty newly diagnosed, treatment-naïve, mild, late-onset AD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This present study therefore devised and assessed a method for simple, fast measurement of finger movements using a tablet application for detecting finger motion (JustTouch; Hitachi Maxell, Tokyo, Japan) to measure the finger motor skills of dementia patients. Several prior studies reported the use of smart terminals for dementia patients, but did not focus on cognitive functions . The assessment of finger motor skills in the present study thus represents a new approach that could ultimately lead to the construction of a measurement system with a smart terminal device that would enable screening of older groups in health classes and other gatherings.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This present study therefore devised and assessed a method for simple, fast measurement of finger movements using a tablet application for detecting finger motion (JustTouch; Hitachi Maxell, Tokyo, Japan) to measure the finger motor skills of dementia patients. Several prior studies reported the use of smart terminals for dementia patients, but did not focus on cognitive functions . The assessment of finger motor skills in the present study thus represents a new approach that could ultimately lead to the construction of a measurement system with a smart terminal device that would enable screening of older groups in health classes and other gatherings.…”
Section: Introductionmentioning
confidence: 97%
“…Several prior studies reported the use of smart terminals for dementia patients, but did not focus on cognitive functions. 8,9 The assessment of finger motor skills in the present study thus represents a new approach that could ultimately lead to the construction of a measurement system with a smart terminal device that would enable screening of older groups in health classes and other gatherings.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that such groups follow different disease trajectories [5,20]. Kuzmickienè and Kaubrys [17] confirmed that executive disorders could have worse effects on ADL and quality of life of patients than memory disorders and explained that the main feature of dysexecutive function is cognitive slowing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, memory decline could predict the transit from normal cognitive functioning to MCI and from MCI to dementia in ACS [13][14][15][16]. However, memory is not the only cognitive function that decline early in Alzheimer's disease [5,8,17]. This has led to investigate whether the combined assessment of episodic memory and other cognitive domains, such as executive functioning, could increase sensitivity and reliability [9,12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Executive dysfunction in MCI and early stage ADRD may be an important but overlooked construct. Executive dysfunction may have significant impact on activities of daily living and quality of life, perhaps more so than memory impairment [57][58][59][60]. We previously demonstrated transitions in performance on traditional executive and attention tasks such as Trailmaking A and B, Block Design, and Visual Retention tests [61] occur up to three years prior to clinical diagnosis of MCI and dementia in individuals who eventually developed AD dementia [12] and Parkinson's disease dementia [62,63].…”
Section: Plos Onementioning
confidence: 99%